Analysis of Applying the Read Answer Discussion Explain and Create (RADEC) Model in Learning to Write Narrative Essays at the Grade V Students of Osi Island State Elementary School - Alerbitu, Nulice; Maipauw, Musa Marsel; Heumassy, Alcytha Pascallia (KnE Social Sciences, 2024)
The learning model and learning materials are one unit that is implemented together at the same time. Choosing the suitable learning model that suits the material for writing narrative essays can help students improve their writing skills. The RADEC learning model (read, answer, discuss, explain, and create) is a learning model that helps teachers in the learning process. This model not only improves students' writing skills in elementary school but also increases writing creativity and encourages students to be able to produce narrative essays. This research aims to describe the application of the RADEC model in learning and students' ability to write narrative essays. The study employs a descriptive qualitative research method. The research results show that applying the RADEC model in teaching writing in the classroom can help students write narrative essays and improve students writing skills. This result was achieved by implementing the RADEC model steps: the teacher provides a reading text containing several questions for students to read and answer; after that, students discuss; next, they present the results of the discussion; and students write narrative essays. The results of applying the RADEC model in learning to write narrative essays show that the ability to write narrative essays of 20 5th-grade students at SD Negeri Pulau Osi was in a good category. Keywords: RADEC model, writing, narrative essay